Airports of the future: essentials for a renewed business model - Macário, Rosário (European Journal of Transport and Infrastructure Research, 2008)
This paper addresses the interaction between airports and airline companies taking into account the evolution of air transport in the last decades and an approach to integrated quality of service. Traditionally airport management, just like all transport infrastructure management, use to look at airlines as their primary customers, due to their legally binding agreements and because airlines pay for several charges, such as landing and parking fees, charges per passenger or tonne of freight handled, etc. Airlines, in turn, have legally binding agreements with passengers and look at passengers as their primary clients. In their unconscious business models airports used to see themselves as providers of an high technological demanding infrastructure, of national strategic interest, for very sophisticated operations where safety played both a very distinguished and distinct role. This paper challenges this traditional airport model and discusses a renewed business model for airports. This renewed model maintains the key functions of an airport but is built in the concept of quality of service as an interactive process that encompasses all agents engaged in the provision of the service.